Facilitated Subcutaneous Immunoglobulin Replacement Therapy in Clinical Practice: A Two Center, Long-Term Retrospective Observation in Adults With Primary Immunodeficiencies - Wiesik-Szewczyk, Ewa; Sołdacki, Dariusz; Paczek, Leszek; Jahnz-Różyk, Karina (Frontiers in Immunology, 2020)
Facilitated subcutaneous immunoglobulin (fSCIG) replacement therapy is the latest method of IgG administration; however, real-life data are limited. We analyzed everyday aspects of fSCIG administration, particularly, the method used to switch from intravenous immunoglobulin (IVIG) or subcutaneous immunoglobulin (SCIG) to fSCIG and the dosing modifications required. Of the 39 adult patients with primary immunodeficiency (PID) who received fSCIG, 34 remained on the therapy at the end of the study. The mean observation time was 18.27 (range, 6–24) months. Two patients were IgG-treatment-naïve; 23 had previously received IVIG and 14 had received SCIG. In 25 cases, a non-ramp-up dosing mode was used to switch to fSCIG (including two half-monthly doses given biweekly in 14 cases, and full monthly doses given in 11 cases), a ramp-up mode was used in six cases; other methods were used in eight cases. The average IgG trough level at baseline was 748 mg/dl (n = 38), 820 mg/dl (n = 32) at Month 6, 843 mg/dl (n = 30) at Month 12, 842 mg/dl (n = 22) at Month 18, and 933 mg/dl (n = 11) at Month 24. No serious bacterial infections or hospitalizations due to PID complications occurred. At the end of the study, 23 patients (67%) received fSCIG every 4 weeks, six (18%) received fSCIG every 3 weeks, and five (15%) received fSCIG biweekly. In conclusion, our study provides real-life evidence of clinical efficacy of the personalized fSCIG treatment when switching from prior immunoglobulin replacement using various switching modes and dosing frequencies